ZAKAT AS A SUPPORTING STATE REVENUE AND EXPENDITURE BUDGET FOR TAXES - Sandy, Niken Baramurti Evieta Enggar; Khusnudin, Khusnudin (Ad-Deenar: Jurnal Ekonomi dan Bisnis Islam, 2025)
This research discusses instruments that can support state revenues apart from taxes in the State Revenue and Expenditure Budget (APBN). Taxes, which are the main source of state income, are in reality still unable to fulfill the APBN, which ultimately has not been able to overcome economic problems in Indonesia, such as the problem of poverty. As a country with the largest Muslim population in the world, one of the instruments that can support the APBN in Indonesia is zakat. This research uses a qualitative research method with a secondary research approach. The aim of this research is to identify other instruments that can replace taxes in supporting the APBN, in this case, Zakat. The results of this research show that zakat cannot completely replace taxes as a supporting instrument for the APBN, due to limitations in its distribution. However, taxes and zakat can go hand in hand to fill each other's gaps and deficiencies in meeting the needs of the State and improving the welfare of society. The difference between this research and similar previous research is that this research discusses other alternative instruments that can help support the APBN apart from taxes. Academically, this research can enrich the literature in the field of public economics by providing a deeper understanding of sources of state income outside of taxes. Meanwhile, practically, this research can provide policy recommendations for the relevant government on optimizing sources of state income other than taxes to increase the sustainability of the APBN.